2013
DOI: 10.1097/icu.0000000000000005
|View full text |Cite
|
Sign up to set email alerts
|

A diagnostic challenge

Abstract: The causes of pupillary dilatation can be unilateral, bilateral, and transient. The clinical approach to dilated pupils requires stepwise evaluation, and based on the findings, unnecessary and costly procedures can be avoided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 43 publications
0
14
0
6
Order By: Relevance
“…Один из механизмов кратковременного угне-тения парасимпатической иннервации зрачка -проникновение в регионарный кровоток мест-ного анестетика [23,40,50], непреднамеренное попадание в конъюнктивальную полость атро-пина [14,65], ипратропия бромида из-под маски небулайзера при параличе мимической мускула-туры [15,16,53,63,70], скополамина и гиосцина при манипуляциях с купирующим тошноту/рвоту пластырем [14,28,39,49,61,76,78], сока луноц-вета, индейского дурмана и бругмансии [5,29,58] и даже порошкообразных стимулирующих пище-вых добавок [46]. В отличие от перечисленных выше фарма-кологических средств, диффузия ботулотокси-на за пределы таргетной зоны при выполнении лечебных или косметических процедур приводит к многонедельному расширению зрачка.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Один из механизмов кратковременного угне-тения парасимпатической иннервации зрачка -проникновение в регионарный кровоток мест-ного анестетика [23,40,50], непреднамеренное попадание в конъюнктивальную полость атро-пина [14,65], ипратропия бромида из-под маски небулайзера при параличе мимической мускула-туры [15,16,53,63,70], скополамина и гиосцина при манипуляциях с купирующим тошноту/рвоту пластырем [14,28,39,49,61,76,78], сока луноц-вета, индейского дурмана и бругмансии [5,29,58] и даже порошкообразных стимулирующих пище-вых добавок [46]. В отличие от перечисленных выше фарма-кологических средств, диффузия ботулотокси-на за пределы таргетной зоны при выполнении лечебных или косметических процедур приводит к многонедельному расширению зрачка.…”
Section: Discussionunclassified
“…Тщательный сбор анамнеза, знание автоном-ной иннервации глазного яблока, причин (как физиологических, так и патологических) разви-тия одностороннего мидриаза позволяют адекват-но оценить этот симптом, существенно ускорить диагностический поиск, исключив необоснован-ные тревожные ожидания пациента и персонала, а также минимизировав выполнение дорогосто-ящих методик нейровизуализации [5,14,36 …”
Section: заключениеunclassified
“…1 In the literature, it is reported that botulism is one of the causes for acquired mydriasis that could be transient or persistent. 2 Stool examination for botulinum toxin in our patient was negative.…”
Section: Discussionmentioning
confidence: 99%
“…Examples of abnormal pupil reflex resulting from neurological problems includes Adie’s tonic pupil, Argyll Robertson Pupil and Horner’s syndrome. Furthermore, dilated pupils that are unresponsive or sluggish are indicative of medical conditions such as oculomotor nerve palsy, trauma, or inflammation (Caglayan et al, 2013). In a clinical setting PLR is examined by observation of the direct response elicited by light in the ipsilateral eye, and consensual response of the contralateral eye (Kaiser et al, 2014).…”
Section: Introductionmentioning
confidence: 99%